TRANSLATION CHALLENGES AND TERMINOLOGICAL ISSUES IN PR DISCOURSE - Karimova Ominaxon Maxmudovna; Arustamyan Y. Y., Arustamyan Y. Y. (Journals Park Publishing, 2025)
In an era of globalized media and multilingual communication, the translation of Public Relations (PR) discourse has become a complex task that extends beyond linguistic transfer. This article investigates the major challenges involved in translating PR materials, with particular focus on specialized terminology, stylistic shifts, and communicative intent in English-Russian translation. Drawing upon Peter Newmark’s functional theory of language, specifically the informative, vocative, and expressive functions, as well as Mona Baker’s narrative theory and views on translator’s activity, the study explores how translators navigate the tensions between semantic precision and persuasive impact. The analysis also engages with the terminological principles outlined by Hudeček and Ćutuk, demonstrating how standardized equivalents and culturally adapted choices shape the reception of PR discourse in target-language contexts. Using a case study approach, the article analyzes three bilingual press releases issued by Samsung, LUKOIL, and UNICEF, representing the domains of technology, corporate sustainability, and humanitarian advocacy. The research identifies dominant strategies, such as literal translation, cultural adaptation, terminological standardization, and stylistic transformation, and evaluates how they support or reshape communicative objectives in translation. The findings affirm that PR translators act not merely as linguistic intermediaries but as active cultural agents, mediating institutional narratives, public perception, and professional norms across languages and cultures.